Perancangan Video Tutorial Teknik Trickshot Bolabasket Berbasis Animasi 3D - Jimmy Pratama; Cristiansen Cristiansen (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
Basketball is a sport that is widely known throughout the world, which was introduced on December 15, 1891 which has continued until now and the existence of the National Basketball Association (NBA) is an association that raises the name of basketball around the world. This trickshot is a basketball movement that is quite difficult to do in terms of style and how to do it because this movement really requires more practice and skill in basketball games but for learning tools in the form of 3d animation videos, there is no such thing. This research produces a short and clear 3-dimensional animation video with a duration of 2 minutes and 3 seconds using the MDLC (Multimedia Development Life Cycle) method which will be implemented on social media such as YouTube and with this animated video, it is hoped that basketball players can add knowledge and insight on how to do the basketball trick shot technique.